Role of inflammation in the pathogenesis of atherosclerosis and therapeutic interventions - Raggi, Paolo; Genest, Jacques; Giles, Jon T.; Rayner, Katey J.; Dwivedi, Girish; Beanlands, Robert S.; Gupta, Milan (Atherosclerosis, 2018)
Rudolph Virchow (1821–1902) recognized inflammation in histological preparations of coronary arteries and proposed that inflammation plays a causal role in atherosclerosis. Despite this seminal observation, the main focus of research and drug development programs has been cholesterol alone, and inflammation received less attention over time. However, during the past several decades extensive observations supported the importance of inflammation in the development and destabilization of atherosclerosis. Studies in patients affected by rheumatological diseases suggested an interaction between chronic inflammation and atherosclerotic cardiovascular disease. Randomized clinical studies with lipid lowering agents suggested that part of the beneficial effect may have been related to reduction in inflammation. More recently, a few studies were designed to directly address the role of anti-inflammatory treatments in reducing risk of atherosclerotic heart disease beyond traditional risk factors. In this article, we review the pathophysiologic contribution of inflammation to atherosclerosis, biomarkers of inflammation and the evidence collected in observational studies regarding the role of chronic inflammation in the development of atherosclerotic heart disease. Finally, we discuss the most recent randomized clinical trials of anti-inflammatory agents directed at stemming atherosclerotic cardiovascular disease.